Supernova - Leong, Fernandez Jun Yi (2019)
Loneliness is common in people of all ages and undoubtedly everyone has experienced it in some capacity at some point in their lives. The need for connection and the pain we feel without it are very humane responses yet this is a topic we often do not want, or even know how, to discuss.